Les évolutions inversées de la multifonctionnalité de l’agriculture et des services environnementaux - Philippe Bonnal; Muriel Bonin; Olivier Aznar (VertigO)
The article focuses on the compared evolution of the use of the notions of multifunctionality and environmental service in agricultural policy. It has been observed that the SE is not a substitute to the MFA, although the concepts of ecosystem and environmental services are strengthening while multifunctionality is disappearing. Different actors have mobilized these two kinds of concepts which have got parallel histories. The reasons for their reverse development paths must be sought in their coherence with the new normative corpus which is emerging at international level and is governing the agricultural, forest and environmental public interventions.